Calculation of liquidity, solvency and profitability against financial performance in industry standards - Padriyansyah; Dimas Pratama Putra (Trigin Publisher, 2023)
This study aims to determine the financial condition of PT. Semen Baturaja Palcxembang using liquidity, solvency, and profitability analysis. Theresearch uses secondary data, namely financial statements from the website of PT. Semen Baturaja. The method for collectingdata used is documentation that includes balance sheets and income statements for 2019-2020. A measuring tool for whether or not the company's condition is used for the purpose of this study, namely by using industry standards. The industry standards used are from Kasmir (2008) and Lukviarman (2006). The results of the study using liquidity analysis, the current ratio showed that in 2019 the ratio value was 2.287 times, so it was in good condition. However, in 2020 the ratio value of 1.33 times indicates that it is in bad condition. The quick ratio in 2019 is in good condition at 1.56 times. Meanwhile, the quick ratio value in 2020 was 1.03 times, which shows that the company is in bad condition. Solvency analysis shows that the debt to asset ratio in 2019 and 2020 was 37% and 40%, meaning it can be assessed as good. Meanwhile, the value of debt-to-equity ratio, in 2019 and 2020 showed not good, namely the ratio value of 59% and 68%. Finally, the profitability ratio is obtained that is considered good where gross profit margin, net profit margin, return on assets, and return on equity financial performance are above industry standards.